2012
DOI: 10.3109/0142159x.2012.702248
|View full text |Cite
|
Sign up to set email alerts
|

Empathy of medical students and personality: Evidence from the Five-Factor Model

Abstract: The main aim of this study was to test hypothetical associations between personality dimensions and empathy scores in medical students. The Portuguese version of NEO-FFI was administered in order to characterize participants in terms of five personality traits: Neuroticism, Extraversion, Agreeableness, Openness to Experience, and Conscientiousness. Self-reported empathy measures were obtained with the Portuguese version of the Jefferson Scale of Physician Empathy (JSPE-spv), a Likert-type questionnaire specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
3
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 27 publications
6
88
3
8
Order By: Relevance
“…', concludes that the evidence from the Schwartz Rounds study conducted with medical students at University College London Medical School demonstrates that offering such educational interventions supports students to be more compassionate, both to themselves and others. However, Magalhaes et al (2012) reported that some students are more empathetic from birth and are therefore more likely to be caring and compassionate in their practice with or without receiving any specific training in compassion. This view was expressed by a sizeable minority of our sample (25%).…”
Section: Discussionmentioning
confidence: 99%
“…', concludes that the evidence from the Schwartz Rounds study conducted with medical students at University College London Medical School demonstrates that offering such educational interventions supports students to be more compassionate, both to themselves and others. However, Magalhaes et al (2012) reported that some students are more empathetic from birth and are therefore more likely to be caring and compassionate in their practice with or without receiving any specific training in compassion. This view was expressed by a sizeable minority of our sample (25%).…”
Section: Discussionmentioning
confidence: 99%
“…A predisposition to attend to the mental states of others (socialcognitive mindreading) is central to agreeableness (Nettle & Liddle, 2008). This trait has been found to relate to the ability to show empathic concern (Magalhães, Costa, & Costa, 2012), the propensity to demonstrate helping behaviors (Graziano, Habashi, Sheese, & Tobin,…”
Section: Active-empathic Listening and The Big-five Factors Of Personmentioning
confidence: 99%
“…This is a thoughtful issue as JSPE has been developed and trialed with the intention of being ''specific for patient care situations '' (Hojat et al 2001) and was adapted to US medical students, whose profile would be probably more equivalent to European 4th year students -nevertheless the JSPE structure has been replicated internationally (Costa et al 2012). However, related to the JSPE, the IRI scale has the limitation of having been developed with no intention to capture the specificities of medical education.…”
Section: Dear Sirmentioning
confidence: 99%